2020
DOI: 10.1111/ases.12796
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of postoperative plasma D‐dimer levels between patients undergoing laparoscopic resection and conventional open resection for colorectal cancer

Abstract: Introduction: D-dimer is widely used in clinical pretests for venous thromboembolism exclusion, and its elevation suggests the presence of thrombus. The extent of hypercoagulability after colorectal surgery has not been systematically compared between patients who have undergone laparoscopic surgery and open surgery. The present study measured D-dimer levels sequentially in patients undergoing colorectal surgery and compared the extent of hypercoagulability between laparoscopic surgery and open surgery. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…26 However, the diagnostic threshold of D-dimer used to predict postoperative VTE in cancer patients is considered to be controversial. 27 Studies have shown that a postoperative D-dimer level of 1 μg/mL is an independent risk factor for VTE in urological tumors. 28 Intravenous ultrasonography in patients with D-dimer levels exceeding 3.3 μg/mL after brain tumor surgery may increase the detection rate of VTE.…”
Section: Clinical Application Value Of the Nomogram Predictive Modelmentioning
confidence: 99%
“…26 However, the diagnostic threshold of D-dimer used to predict postoperative VTE in cancer patients is considered to be controversial. 27 Studies have shown that a postoperative D-dimer level of 1 μg/mL is an independent risk factor for VTE in urological tumors. 28 Intravenous ultrasonography in patients with D-dimer levels exceeding 3.3 μg/mL after brain tumor surgery may increase the detection rate of VTE.…”
Section: Clinical Application Value Of the Nomogram Predictive Modelmentioning
confidence: 99%
“…Colorectal cancer is the third most common cancer worldwide [1]. En bloc radical excision of primary tumor and regional lymph nodes by open or laparoscopic surgery, with or without neoadjuvant chemo-radiotherapy, remains the gold-standard treatment, providing cure or longterm disease-free survival with a good quality of life [2,3]. After resection, anastomotic reconstruction to restore colorectal continuity is a general procedure to realize its physiological function in complex gastrointestinal surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Severe elevation is associated with a worse outcome and elevated D-Dimer levels represent a poor prognostic factor [10,11]. D-Dimer is a fibrin degradation product and elevated D-Dimer levels can be observed during deep vein thrombosis (DVT) and pulmonary embolism (PE), but also in other clinical conditions such as injuries, after surgery, during infection and inflammation or cancer [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%